Numerical study of droplet vaporization - Tan, Edwin Hongwei (Nanyang Technological University, 2021)
Droplet vaporisation is one of the factors people are looking into to understand more on how respiratory infections happens which allows the governing bodies to come out with guideline to prevent and control the spread globally. As the coronavirus 2019 (COVID-19) outbreak, paper have been done on how the droplet travels with influence of wind speed and relative humidity (RH) to validate the social distancing guideline (1.83m/6 feet apart) gave by World Health Organisation (WHO). However, the paper uses the same particle injection velocity which will affect the particle travel with the influence of ambient wind. A transient species transport model will be used to study the droplet vaporisation with the injection velocity of 22m/s (highest cough velocity) and 11.2m/s (average cough speed) at varying constant wind speed of 0m/s to 3m/s blowing in the horizontal and lateral direction. Due to time constraint in developing the current model, RH factor was not set therefore the default is being used. The numerical results indicate that with a lower injection velocity, the droplet vaporisation is lower compared to the higher injection velocity. It also indicates that for 11.2m/s injection velocity with the wind velocity of 0m/s to 2m/s particles distance travel is much lesser at 2 second compared to 22m/s. Although the particles distance travel is lesser, but at both injection speed, it still exceeds the recommended social distancing guideline after 2 seconds.